1990
DOI: 10.1128/jb.172.2.1014-1018.1990
|View full text |Cite
|
Sign up to set email alerts
|

The GLN3 gene product is required for transcriptional activation of allantoin system gene expression in Saccharomyces cerevisiae

Abstract: We show that mutation at the GLN3 locus results in decreased steady-state levels of DAL7, DUR1,2, CAR], and URA3 mRNAs derived from cultures grown in the presence of inducer. Basal levels of these RNA species, however, were not significantly affected by a gln3 mutation. The GLN3 product appears to affect gene expression in two ways. The pleiotropic requirement of GLN3 for induced gene expression probably derives from the need of the GLN3 product for inducer uptake into the cell and its loss in gln3 mutants. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
57
0

Year Published

1991
1991
2003
2003

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 23 publications
3
57
0
Order By: Relevance
“…For example, they may be incapable of absorbing USA due to a mutation of the DAL5 transporter gene (Turoscy and Cooper, 1987) or of GLN3, which encodes a transcription factor required for DAL5 transcription (Cooper et al, 1990;Mitchell and Magasanik, 1984). Alternatively, the cells may be able to absorb USA but be unable to convert it into uracil due to mutation of a gene required for uracil biosynthesis downstream of the USA step, such as the URA3 gene.…”
Section: Mutants Defective For the Propagation Of [Ure3]mentioning
confidence: 99%
“…For example, they may be incapable of absorbing USA due to a mutation of the DAL5 transporter gene (Turoscy and Cooper, 1987) or of GLN3, which encodes a transcription factor required for DAL5 transcription (Cooper et al, 1990;Mitchell and Magasanik, 1984). Alternatively, the cells may be able to absorb USA but be unable to convert it into uracil due to mutation of a gene required for uracil biosynthesis downstream of the USA step, such as the URA3 gene.…”
Section: Mutants Defective For the Propagation Of [Ure3]mentioning
confidence: 99%
“…For instance, in cells grown under conditions of nitrogen derepression, high-level expression of the allantoate permease gene DAL5 is largely dependent on Gln3p (Cooper et a/., 1990). Gln3p-activated expression is sensitive to nitrogen repression (Mitchell and Magasanik, 1984;Magasanik, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Parallel evidence showed that the nonchromosomal gene [PSI] is a prion form of Sup35p (10). Ure2p is a regulator of nitrogen catabolism that acts in the cytoplasm by complexing with the GATA transcription factor Gln3p, preventing entry of the latter into the nucleus (12)(13)(14)(15)(16)(17)(18). Ure2p suffices to carry out the prion domain functions (19,20), but Ure2p 1-80 is even more efficient (21).…”
mentioning
confidence: 99%